2021
DOI: 10.3389/fphys.2021.690696
|View full text |Cite
|
Sign up to set email alerts
|

New Insight Into the Cardioprotective Effects of Allium ursinum L. Extract Against Myocardial Ischemia-Reperfusion Injury

Abstract: This study aimed to estimate the effects of increasing doses of Allium ursinum methanol extract on cardiac ischemia/reperfusion injury (I/R) with a special emphasis on the role of oxidative stress. Fifty rats were randomly divided into five groups (10 animals per group) depending on the applied treatment as follows: sham, rats who drank only tap water for 28 days and hearts were retrogradely perfused for 80 min without I/R injury, I/R, rats who drank only tap water for 28 days and hearts were exposed to ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…In addition to the sulfur compounds, biomolecules such as peptides, flavonoids, phenols, alkaloids, and saponins contribute to the antimicrobial activity of Allium species or reveal synergistic effects with other present bioactive compounds [ 7 , 26 ]. Polyphenolic compounds have great structural diversity and variations in chemical composition and thus differ in their antibacterial effectiveness against pathogenic microorganisms [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the sulfur compounds, biomolecules such as peptides, flavonoids, phenols, alkaloids, and saponins contribute to the antimicrobial activity of Allium species or reveal synergistic effects with other present bioactive compounds [ 7 , 26 ]. Polyphenolic compounds have great structural diversity and variations in chemical composition and thus differ in their antibacterial effectiveness against pathogenic microorganisms [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies support the fact that A. ursinum can be used as a natural antimicrobial agent. However, previous studies have shown conflicting results regarding the antimicrobial activity of A. ursinum extracts against various Gram-positive and Gram-negative bacteria [ 7 , 8 , 31 , 32 , 33 ]. As it was stated before, this can be explained by the isolation of different active compounds using different solvents during extraction, extraction method, plant origin and plant part.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters of heart function were recorded via a pressure transducer attached to a data acquisition system and displayed using the included software. Prior to performing experiments, the balloon was checked for filling capacity and transducer calibration was performed according to the manufacturer's instructions (Rankovic et al 2021).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…The degree of lipid peroxidation in the coronary venous effluent was estimated by measuring TBARS, using 1% thiobarbituric acid in 0.05 M NaOH, which was incubated with the coronary effluent at 100 • C for 15 min and measured at 530 nm. The Krebs-Henseleit solution was used as a blank probe (Rankovic et al 2021).…”
Section: Tbars Determination (Index Of Lipid Peroxidation)mentioning
confidence: 99%